Risk control simulation of the closed-loop supply chain of waste electrical and electronic equipment based on system dynamics - Zheng, Rong; Huang, Zuqing; Wu, Zhen (Frontiers in Energy Research, 2022)
Recycling and remanufacturing waste electrical and electronic equipment (WEEE) can promote the comprehensive utilization of resources and promote the development of the circular economy. However, there are associated risks involved. This study explored the effectiveness of risk control in the WEEE closed-loop supply chain to provide decision support in the sustainable development of WEEE. The catastrophe progression method was used for risk evaluation, and the WEEE risk control model was constructed using system dynamics to analyze the influence of risk control strategies. The results show that adopting risk control strategies positively promotes risk control. Risk mitigation is most pronounced when both the fund subsidy and the green and low-carbon strategies are adopted. When only one approach is implemented, the green and low-carbon strategy has a more considerable effect. When the intensities of the mitigation measures are improved to the same extent, the risk control effect generated by the fund subsidy strategy was found to have a greater impact. The findings provide a useful reference for formulating subsequent risk control strategies in the WEEE closed-loop supply chain.